Developing Preschool Language Surveillance Models - Cumulative and Clustering Patterns of Early Life Factors in the Early Language in Victoria Study Cohort - Patricia Eadie; Penny Levickis; Penny Levickis; Cristina McKean; Elizabeth Westrupp; Elizabeth Westrupp; Edith L. Bavin; Edith L. Bavin; Robert S. Ware; Bibi Gerner; Bibi Gerner; Sheena Reilly (Frontiers Media S.A., 2022)
BackgroundScreening and surveillance of development are integral to ensuring effective early identification and intervention strategies for children with vulnerabilities. However, not all developmental skills have reliable screening processes, such as early language ability.MethodWe describe how a set of early life factors used in a large, prospective community cohort from Australia are associated with language abilities across the preschool years, and determine if either an accumulation of risk factors or a clustering of risk factors provide a feasible approach to surveillance of language development in preschool children.ResultsThere were 1,208 children with a 7-year language outcome. The accumulation of early life factors increased the likelihood of children having low language skills at 7-years. Over a third of children with typical language skills (36.6%) had ≤ two risks and half of the children with low language (50%) had six or more risks. As the number of factors increases the risk of having low language at 7-years increases, for example, children with six or more risks had 17 times greater risk, compared to those with ≤ two risks. Data collected from 1,910 children at 8- to 12-months were used in the latent class modeling. Four profile classes (or groups) were identified. The largest group was developmentally enabled with a supportive home learning environment (56.2%, n = 1,073). The second group was vulnerable, both developmentally and in their home learning environment (31.2%, n = 596); the third group was socially disadvantaged with a vulnerable home learning environment (7.4%, n = 142); the final group featured maternal mental health problems and vulnerable child socio-emotional adjustment (5.2%, n = 99). Compared to developmentally enabled children, the risk of low language at 7-years was greater for children in the three other groups.ConclusionThe cumulative and cluster risk analyses demonstrate the potential to use developmental surveillance to identify children within the first years of life who are at risk of language difficulties. Importantly, parent-child interaction and the home learning environment emerged as a consistent cluster. We recommend they be adopted as the common focus for early intervention and universal language promotion programs.